Performance Metrics in Supply Chain Management. Evidence from Romanian Economy - Alexandru Constăngioară (Amfiteatru Economic)
The proposed empirical research uses a national sample of 19 Romanian companies from various industries to estimate de utilities for financial and non-financial performance measures used in Romanian supply chains. Empirical findings show that national supply chain measurement systems are balanced, using both financial and non-financial performance measures. The high estimated utility corresponding to indicators measuring logistic costs provides evidence that inter-functional and inter-organization integration in supply chains at national level are realized through operational excellence. Achieving the full potential of supply chain integration requires that management fosters both integration of operations and integration of customers.